2006
DOI: 10.1021/ic0515352
|View full text |Cite
|
Sign up to set email alerts
|

NMR and EPR Studies of Chloroiron(III) Tetraphenyl-chlorin and Its Complexes with Imidazoles and Pyridines of Widely Differing Basicities

Abstract: The NMR and EPR spectra of two bis-imidazole and three bis-pyridine complexes of tetraphenylchlorinatoiron(III) ,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(23 citation statements)
references
References 87 publications
3
20
0
Order By: Relevance
“…Based on the TDDFT calculation it is difficult to distinguish between FeTPP(Pyr) 2 which in turn suggests that FeTPP(Pyr)Cl is present in neat pyridine solution. This conclusion is in agreement with NMR studies of related adducts of tetraphenylchlorin with a series of basic ligands [40]. Pyridine is a relatively weak base and is therefore unlikely to displace the Cl − ion here.…”
Section: Spectroscopic Characteristics Of the Ligated Forms Of Mtppsupporting
confidence: 90%
“…Based on the TDDFT calculation it is difficult to distinguish between FeTPP(Pyr) 2 which in turn suggests that FeTPP(Pyr)Cl is present in neat pyridine solution. This conclusion is in agreement with NMR studies of related adducts of tetraphenylchlorin with a series of basic ligands [40]. Pyridine is a relatively weak base and is therefore unlikely to displace the Cl − ion here.…”
Section: Spectroscopic Characteristics Of the Ligated Forms Of Mtppsupporting
confidence: 90%
“…Spectroscopic analysis and density functional theory calculations of variously substituted ferriporphyrin and ferrichlorin model compounds indicate that the ruffling of a ferriheme stabilizes the d xz and d yz orbitals of the iron and changes the electron configuration of low-spin Fe 3þ from the more common ðd xy Þ 2 ðd xz ;d yz Þ 3 to the less common ðd xz ;d yz Þ 4 ðd xy Þ 1 configuration (48)(49)(50)(51)(52)(53). This change in configuration causes major changes in the 1 H-NMR chemical shifts of the β-pyrrole substituent and meso-H signals of the heme (48)(49)(50)(51)(52). In ruffled heme, the p z orbital from the porphyrin 2a 2u ðπÞ orbital twists away from orthogonality with the porphyrin plane to permit interaction of the 2a 2u ðπÞ orbital with the 3d xy orbital of the iron.…”
Section: Discussionmentioning
confidence: 99%
“…This reorganization of the spin density in highly ruffled model complexes is believed to be a consequence of a ground state electron configuration change from ( d xy ) 2 ( d xz,yz ) 3 to ( d xz,yz ) 4 ( d xy ) 1 caused by preferential stabilization of the Fe 3 d xz - and 3 d yz -based molecular orbitals (MOs) by strong π-acceptor axial ligands based upon ligand field theory (LFT) arguments. However, in biological systems when there has been a comparison of more planar and more ruffled six-coordinate hemes, the NMR results have not been consistent with a ground state electron configuration change 5,10,11,35,36. Instead, these studies have observed a decrease of the average heme methyl 1 H shift for increased heme ruffling.…”
Section: Introductionmentioning
confidence: 88%